Does work-based learning facilitate transitions to decent work? - Brewer, Laura; Comyn, Paul (Geneva, 2018)
"In 2012, the International Labour Conference issued a resolution with a call for action to tackle the unprecedented youth employment crisis through a set of policy measures. The resolution provides guiding principles and a package of inter-related policies for countries wanting to take immediate and targeted action to address the crisis of youth labour markets. This paper, is part of follow-up action on knowledge building co-ordinated by the ILO’s Youth Employment Programme (YEP). In the current global context of complex economic challenges, skills and employability have emerged as a key priority for policy makers. In this context, the need for more effective work-based learning practices has become increasingly important. This paper examines the different forms of work-based learning, and takes stock of available data on the labour market impact such schemes where they exist. It considers structured apprenticeships, internships, traineeships and other programmes that include a work-based learning component. The paper finds evidence of positive impacts of formal structured work-based learning, and argues that future efforts should encourage engagement with private sector firms in creating and expanding such structured opportunities for young people."